Proof of Intent in Aiding and Abetting a Criminal Act in Medan District Court Decision Number 882/Pid.B/2024/PN Mdn: Pembuktian Pemenuhan Unsur Kesengajaan Pembantuan Tindak Pidana Pada Putusan Pengadilan Negeri Medan Nomor 882/Pid.B/2024/PN Mdn - Arrifa, Reisa; Adhari, Ade (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Accomplice liability under Article 56 of the Indonesian Criminal Code requires proof of intent, reflected in the accomplice’s knowledge and will to facilitate a crime. Specific Background: In Decision No. 882/Pid.B/2024/PN Mdn, the court concluded that intent in accomplice liability was not established, despite evidence showing the defendant knowingly created and transferred mobile banking accounts to a fraud perpetrator for financial gain. Knowledge Gap: Existing studies rarely examine inconsistencies between doctrinal constructions of intent and their judicial application in accomplice liability within fraud cases. Aims: This study analyzes how the element of intent in accomplice liability was assessed and whether the court’s reasoning aligns with criminal law doctrine. Results: Findings indicate that the defendant’s conduct demonstrates knowledge and purposeful assistance fulfilling the subjective elements of fraud under Article 378 KUHP and the intent requirement of Article 56 KUHP. Novelty: This study provides a doctrinal–case analysis showing that judicial misinterpretation of intent can blur the distinction between neutral acts and intentional facilitation. Implications: The results highlight the need for consistent judicial application of mens rea principles to maintain the integrity of criminal responsibility and prevent erroneous exclusions of accomplice liability. Highlights: The case reveals a doctrinal inconsistency in assessing intent for accomplice liability. Evidence shows the defendant’s actions met the subjective elements of fraud. Misinterpretation of mens rea risks weakening the boundaries of criminal responsibility. Keywords: Accomplice Liability, Intent, Article 378 KUHP, Proof, Participation in Crime